An Analysis On Takaful Operation Under Conventional Regulator: A Sri Lankan Experience - Mohamed Mazahir, Seyed Mohamed; Ab Rahman, Asmak; Ramzy, Mohammad Ismath (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
In this contemporary world, insurance plays a significant role in the affairs of a human being. It has become inevitable in the life of people. This study aimed at analysing the operations of Takāful (Islamic insurance) companies that are regulated by the Civil Law and finding their core regulatory issues in Sri Lanka. This study highlights the role of Sharīʻah Advisory Council in Takāful industry in Sri Lanka as this council formulates policies and guidelines, and ensures the investment and operation in line with Sharīʻah principles. The research also discusses core issues relating to Islamic insurance such as operation, investment, reporting and separation of funds. It argues that there is a need for the Muslim Leaders as well as the Sharīʻah scholars, Takāful operators and academics to be effectively involved in designing a framework for Takāful regulations in Sri Lanka. Finally, the research recommends the establishment of a regulatory council that will be responsible for the formulation of Takaful Law in that will be similar to that of the Malaysian Islamic Financial Service Act 2013 (IFSA), in Sri Lanka.